Profile and validity of PBL-SETS interactive multimedia to train learners' science literacy - Siti Addinul Nasihah; I. Isnawati; Hasan Subekti (University of Muhammadiyah Malang, 2024)
The background of this research is the low science literacy of Indonesian students based on PISA results caused by non-contextual learning and conventional methods. This study aims to develop and validate an interactive multimedia program based on the Problem-Based Learning-Science, Environment, Technology, and Society (PBL-SETS) approach to train students' science literacy. This research uses an R&D (research and development) approach with define, design, develop, and disseminate (4D) model, which is limited to only the validation stage of development. Although many studies have shown the effectiveness of interactive multimedia in improving science literacy, the combination of PBL, SETS, and interactive multimedia still needs to be researched, especially in Indonesia. The results showed that the developed PBL-SETS interactive multimedia had very valid criteria, with an overall average score of 94.15%. These results indicate that PBL-SETS interactive multimedia is valid and feasible to be used as a learning alternative to train students' science literacy in school.